Viajantes, século XIX: negras escravas e livres no Rio de Janeiro - Queiroz, Maria Isaura Pereira de (Revista do Instituto de Estudos Brasileiros, 1988)
The narratives of travelers can be particularly useful when the definition of the first problems are being searched, in a research field still unexplored; it is the case of relationship among Black and mulatto women in Brazil, during the 19th Century. This essay shows the utility of these sources; it reveals also that in the interior of the slave's collectivity did exist different levels; it directs the attention, finally, to the kind of relationship that existed among Black and mullato woman, when they were slaves and they were free.